2013
DOI: 10.5688/ajpe776125
|View full text |Cite
|
Sign up to set email alerts
|

Student Engagement in Pharmacology Courses Using Online Learning Tools

Abstract: Objective. To assess factors influencing student engagement with e-tools used as a learning supplement to the standard curriculum in pharmacology courses. Design. A suite of 148 e-tools (interactive online teaching materials encompassing the basic mechanisms of action for different drug classes) were designed and implemented across 2 semesters for thirdyear pharmacy students. Assessment. Student engagement and use of this new teaching strategy were assessed using a survey instrument and usage statistics for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
2
22
2
Order By: Relevance
“…[20][21][22] In contrast to Karaksha et al's findings, 22 we found that a significantly larger proportion of students accessed the modules during scheduled times in the Level 1 course than in any of the courses that followed. For each of the four courses, we found a statistically significant difference in frequency of access to the modules in relation to proximity to course evaluations, with students tending to use the modules more frequently as they approached the That study also found that, similar to self-directed courses, self-reported and observed access frequency to electronic resources peaked from 7 to 11 pm and in the days immediately preceding a course evaluation.…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…[20][21][22] In contrast to Karaksha et al's findings, 22 we found that a significantly larger proportion of students accessed the modules during scheduled times in the Level 1 course than in any of the courses that followed. For each of the four courses, we found a statistically significant difference in frequency of access to the modules in relation to proximity to course evaluations, with students tending to use the modules more frequently as they approached the That study also found that, similar to self-directed courses, self-reported and observed access frequency to electronic resources peaked from 7 to 11 pm and in the days immediately preceding a course evaluation.…”
Section: Resultscontrasting
confidence: 83%
“…In those three studies, more complete utilization (e.g., time and duration of use of modules) data were not objectively recorded-only time of access. [20][21][22] In contrast to Karaksha et al's findings, 22 we found that a significantly larger proportion of students accessed the modules during scheduled times in the Level 1 course than in any of the courses that followed. In the first course, more than half of the participating students accessed the modules at least once during the designated scheduled times.…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…It has also been found to be contributory to key learning outcomes by enhancing student exam performance 2 . Furthermore, online teaching and learning resources are effective in increasing student engagement with proper motivation and reminder 3 . Online quizzing is an active pedagogical technique as it enables faculty to reflect about the effectiveness of various teaching and assessment practices on student engagement, performance and perception 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This is closely associated with the verification and research content; there is a disconnection between the training content and the requirements of pharmaceutical jobs for vocational education graduates. Several new teaching methods were tried in this area, such as simulative drugstore, cases based learning and online teaching (Gang & Li, 2012;Gupta, Arora, & Kaushal, 2014;Karaksha, Grant, Anoopkumar, Nirthanan, & Davey, 2013). Therefore, this paper through the exploration of pharmacology teaching methods reform, changes the traditional mode that is centered as the validation of drug pharmacological activity to the new teaching mode as the center of clinical medication and pharmacy services.…”
Section: Introductionmentioning
confidence: 99%